Experimental Study of Three-Dimensional Propagation of Crack in Transparent Rock Mass - Zhende Zhu; Yuan Tian; Xinyu Liu (Advances in Civil Engineering)
Three-dimensional crack propagation in a rock mass was investigated using a specifically designed material with good transparency and elastoplasticity. The material has properties that are similar to those of the nature sandstone. Hydromechanical tests were conducted to simulate pore pressure in the paper to study the influence of the angle of the primary crack and the water pressure on the mechanical stability of the rock mass. The results indicated that the water pressure accelerated the crack propagation and the failure of the samples. The influence of water pressure on initiation crack strength was not significant but had a significant impact on the peak strength. With the increase in water pressure, the crack initiation strength, penetration strength, and peak strength all decrease in varying degrees. The penetration strength did not only depend on the pore pressure but also exhibited high sensitivity to the inclination angle of the primary crack. The extended finite element method is used to simulate hydraulic fracturing. The simulation results show that the stress near the tip exhibited a cycle of energy accumulation-crack expansion-stress relaxation as the crack expanded, and this finding was consistent with Griffith’s energy theory.